Pengaruh Disiplin Kerja Pegawai terhadap Kualitas Pelayanan Publik Pemerintahan Desa Dikecamatan Bongomeme Kabupaten Gorontalo - Sity Febrianty Wange; Rustam Tohopi; Yakop Noho Nani (Mahesa Research Center, 2023)
This study aims to determine the effect of employee discipline on the quality of village government publik services in Bongomeme Sub-district, Gorontalo Regency. The research uses a quantitative approach. The type research data is primary. The samples are 58 people. Data collection techniques are carried out by distributing questionnaires to employees. The analysis test showed that better work discipline would improve the quality of publik services in the village government in Bongomeme Sub-district, Gorontalo Regency. The result of the t-count test show that employee work discipline has a positive and significant effect on the quality of village government publik services in Bongomeme Sub-district, Gorontalo Regency. Thus the first hypothesis (Ha) can be proven and accepted. The result of the coefficient of determination test obtained an R square value of 0.152 or 15.2% of the independent variable X (Employee Work Discipline) contributing to the Y variable (Quality of Publik Services), while the remaining 0.848 or 84.45% is from other factors which are not examined such a compensation, work culture, participation and leadership